PEMROGRAMAN SISTEM PENGAMAN RUMAH OTOMATIS YANG TERHUBUNG DENGAN TELEPON SELULER BERBASIS MIKROKONTROLER ATMEGA8 DAN ATMEGA162 - Pratama, Donny; Subali, Subali (Gema Teknologi, 2012)
Donny Pratama, Subali, in paper programming of auto home security system connected to mobile phone based on microcontroller ATMEGA8 and ATMEGA162 explain that in modernization era, almost all using automation tools, both in industrial, office, especially at home. Especially with the advance of age more unemployment also exist. With so many unemployed crime was more rampant. Therefore, the security of the home and its contents is very necessary for every homeowner. Especially when the house in a discharged condition or homeowners are doing activities outside the home. Home security system that uses a microcontroller-based mobile phone as a medium of information is a tool that is needed in every home. Where this system in any room in the home will attach several sensors are used to monitor the condition of the house. The sensors used include PIR sensor (Passive Infra - Red) to detect motion, gas sensors to detect a gas leak and also uses a temperature sensor to determine the temperature of the room. All these sensors are programmed according to the function of each tool. And as a basic programming language used compiler (Bascom) to support the work of all the sensors. For sensor work will then be processed by a microcontroller which will then be sent the information to a cell phone via a modem homeowners. Keyword : home security systems, mobile telephone, microcontroller, ATMEGA8, ATMega162